2021
DOI: 10.2196/32856
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the World Inflammatory Bowel Disease Day and Crohn’s and Colitis Awareness Week on Population Interest Between 2016 and 2020: Google Trends Analysis

Abstract: Background More than 6 million people are affected by inflammatory bowel disease (IBD) globally. The World IBD Day (WID, May 19) and Crohn’s and Colitis Awareness Week (CCAW, December 1-7) occur yearly as national health observances to raise public awareness of IBD, but their effects are unclear. Objective The aim of this study was to analyze the relationship between WID or CCAW and the public health awareness on IBD represented by the Google search eng… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 23 publications
2
10
0
Order By: Relevance
“…Our research work demonstrates the potential of analyzing user activity collected through Google and GT. Our results concur with those of prior research (33,36,40,43), and it emphasizes the importance of OHISB evaluation in current days for raising public awareness of specific health issues (37,(40)(41)(42)(43)(44)(45). Furthermore, our study is novel as it evaluates the impact of OHISB on the WDMD considering selected European countries and depending on whether they have NPHs or not, their healthcare system model, and the prevalence of DM among the population.…”
Section: Discussionsupporting
confidence: 91%
“…Our research work demonstrates the potential of analyzing user activity collected through Google and GT. Our results concur with those of prior research (33,36,40,43), and it emphasizes the importance of OHISB evaluation in current days for raising public awareness of specific health issues (37,(40)(41)(42)(43)(44)(45). Furthermore, our study is novel as it evaluates the impact of OHISB on the WDMD considering selected European countries and depending on whether they have NPHs or not, their healthcare system model, and the prevalence of DM among the population.…”
Section: Discussionsupporting
confidence: 91%
“…Of note, the RSVs for breast, lung, and prostate cancers in the U.S. shot up around the 15th week of 2020, when the COVID-19 pandemic began, although BCAM continued to be associated with increasing RSVs of breast cancer in 2020, unlike the other two awareness months. The dramatic increases in the RSVs for the cancers could be related to concerns among the general public that those who are immunocompromised might be more vulnerable to COVID-19, as seen in the data set in inflammatory bowel diseases [24]. However, contrasting data from Canada showed that interest in various cancers temporarily decreased during the early pandemic [27].…”
Section: Discussionmentioning
confidence: 99%
“…Google Trends, a publicly available data source generated based on the total Google search data [10], has been utilized for social and behavioral health research [11][12][13][14][15][16][17][18][19][20][21][22][23][24]. This analysis enables us to determine the relative popularity of specific search terms in a particular category (for example, "health"), place, and time range, suggesting how popular the terms are at a specific time point.…”
Section: Data Source and Definitionmentioning
confidence: 99%
“…Moreover, chronic inflammation in IBD has been associated with serious, often fatal comorbidities, including cancer, cardiovascular diseases, and liver diseases [ 11 , 12 ]. The rate of incidence of IBD has been rising dramatically since the industrial revolution, with a current global burden of more than 6 million people [ 13 ]. Although the IBD etiology remains largely unknown, it has been hypothesized that the industrial lifestyle, which includes increased use of antibiotics and a diet rich in highly processed foods, has resulted in detrimental changes to the intestinal microbiota that significantly contribute to disease risk [ 9 , 14 ].…”
Section: Introductionmentioning
confidence: 99%